2019
DOI: 10.28918/jupe.v16i1.1822
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study aims to analyze the values of nationalism materials in Islamic boarding schools. So far there has been a judgement believing that Islamic boarding schools are the center of radicalism in Indonesia. The militancy and aggressiveness of radicals are considered as the impact of education carried out in Islamic boarding schools. This study refutes research findings that assess Islamic boarding schools as the basis of radicalism. Through a study of the curriculum, books and teachings carried out in Islami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…Last but not least, it is known that the moderately hydrophilic surface better facilitated rBMSC adhesion and spreading and changes in the cell morphology has become a vital factor in osteogenic differentiation because it can successfully stimulate downstream signals/genes such as the integrin signal, focal adhesion, and actin organization. 56 However, P20T1 and P10T1 exhibited similar cell morphology (the cell area in Figure 6b did not show a significant difference between P20T1 and P10T1, p > 0.05), which indicated that cell morphology was not the main reason why rBMSCs cultured on P10T1 show higher osteogenic differentiation. Therefore, the increase in osteogenic differentiation might be related to the content of TCP sol favoring rBMSC proliferation.…”
Section: Improved Wettability and Mechanicalmentioning
confidence: 85%
See 1 more Smart Citation
“…Last but not least, it is known that the moderately hydrophilic surface better facilitated rBMSC adhesion and spreading and changes in the cell morphology has become a vital factor in osteogenic differentiation because it can successfully stimulate downstream signals/genes such as the integrin signal, focal adhesion, and actin organization. 56 However, P20T1 and P10T1 exhibited similar cell morphology (the cell area in Figure 6b did not show a significant difference between P20T1 and P10T1, p > 0.05), which indicated that cell morphology was not the main reason why rBMSCs cultured on P10T1 show higher osteogenic differentiation. Therefore, the increase in osteogenic differentiation might be related to the content of TCP sol favoring rBMSC proliferation.…”
Section: Improved Wettability and Mechanicalmentioning
confidence: 85%
“…It is consistent with the reason that the MSCs cultured on O 3 −Ti samples showed a higher degree of osteogenic differentiation than those of Ti in the research of Sunarso et al due to cell−cell contact. 56 In addition, more calcium ions dissolved from TCP sol might activate the calcium-dependent pathway, thereby stimulating the osteogenic differentiation of rBMSCs cultured on P10T1. 58 Moreover, as mentioned earlier, the incorporation of 9.1 wt % TCP sol accelerated the formation of mineral layers, and it is believed that, in the physiological environment, the minerals on the surface of the scaffold are the basis for cell differentiation and new bone formation.…”
Section: Improved Wettability and Mechanicalmentioning
confidence: 99%
“…Ding et al 184 compared sandblasted and acid-etched zirconia implants with commercial Ti implants, and animal experiments showed that the osteogenesis ability of the zirconia implants was comparable to that of commercial Ti implants. The research of Feng et al 185 and Sunarso et al 186 showed that sandblasting and acid etching can also promote the adhesion of bone cells on the surface of PEEK and enhance osseointegration. However, some negative effects should also be paid attention to; sandblasted material is often embedded in the surface and may interfere with osseointegration after implantation if not removed, and acid etching may reduce the implant fatigue resistance due to microcracks on the surface.…”
Section: Factors Affecting the Survival Rate Of Raimentioning
confidence: 99%
“…Pull-out strength testing did not show a statistical difference between the three samples tested, although TLR had higher mechanical properties. From these results, the authors proposed that the material containing the monoaromatic dimethacrylate (PCDMA) with greater hardness and elastic modulus values may be applied as an alternative to the bis-GMA-based adhesive [29,69,70]. This review summarizes the most significant attributes of polymers while also outlining the importance of BPA-free and smart materials.…”
Section: Novel Bpa-free Composite Adhesivesmentioning
confidence: 99%